2020
DOI: 10.3390/jcm9072076
|View full text |Cite
|
Sign up to set email alerts
|

The Association between High Body Mass Index and Early Clinical Outcomes in Patients with Proximal Femur Fractures

Abstract: Background: Fractures of the proximal femur constitute daily work in orthopedic trauma surgery. With the continuous increase of obesity in the general population, surgeons face several known technical challenges. The aim of this study was to investigate the association of high body mass index (BMI) in patients with proximal femur fractures with intra- and postoperative adverse events, as well as with functional outcomes after successful surgery. Methods: In this retrospective, single-center cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…Five studies were meta-analyzed for the risk of short-term (≤ 30-day) mortality after hip fracture surgery [ 18 , 23 26 ]. The OR was 0.63 (95% CI: 0.58–0.68; P < 0.00001) for short-term mortality in the group with obesity compared with the average-weight group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were meta-analyzed for the risk of short-term (≤ 30-day) mortality after hip fracture surgery [ 18 , 23 26 ]. The OR was 0.63 (95% CI: 0.58–0.68; P < 0.00001) for short-term mortality in the group with obesity compared with the average-weight group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As obesity becomes a more common diagnosis within the hip fracture patient population, it becomes necessary to develop a standardized intraoperative approach to positioning to care for this specific patient population to avoid the known increased risk of complications [14][15][16][17]. A recent study by Bekeris et al reported an increased incidence of comorbidities, including obesity amongst hip fracture patients, and Sems et al reported increased complication rates following surgical fixation of pelvic ring injuries in obese patients [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Bekeris et al reported an increased incidence of comorbidities, including obesity amongst hip fracture patients, and Sems et al reported increased complication rates following surgical fixation of pelvic ring injuries in obese patients [14,15]. Furthermore, a study of 950 patients by Muller et al reported that increased BMI in patients with hip fractures is associated with both longer operation time and length of hospitalization [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from the initial radiological evaluation in lieu of the thickened soft tissues, especially around the proximal femur to the follow-up, the care of obese patients must be optimised in a multidisciplinary manner 3. The most common problems and complications reported in obese patients suffering from femur fracture are prolonged operative duration, longer length of stay in hospital, wound infections, revision surgeries and some systemic complications 4–6. Furthermore, special surgical equipment, including larger and stronger tables, special supports, as well as specially designed instruments, are usually required 1.…”
Section: Introductionmentioning
confidence: 99%